pH Contribution on the Removal of T oxic lons from Aqueous Solutions - Navarro, Abel E. (2005)
The contribution of the pH on the bio-removal of heavy metals is evaluated from two points of view: the metallicion, by means of use of ions with the same charge, and that of the biosorbent, using several natural biosorbents on the adsorption of a common metal. The results show a strong pH effect in the metallic ion's aqueous chemistry, dueto a complex chemical speciation dominated by aquo and hydroxo-complexes, which is partially conditioned by the own cation's acidity. The characteristically functional groups, present on the adsorbent's surface, are also subject to pH effect, because of the strong competence with exchangeable ions (H3O+ ) for the ionizables active centers. lt has been experimentally proved the preference of the studied biosorbents for Cd +2 ion rather than Zn +2 , being the algae Lessonia trabeculata, polyalginaterich algae, in its both varieties, non and cross-linked, who reports the maximum adsorption capacity (q = 260.5 mg/g). Cation's acidity and functional groups on adsorbent's surface are proposed like the responsible issue for the selectivity and efficiency of the process.